Hydrogen storage nano composite material and powder preparation equipment and preparation method
By using Tix(LaaCebMgc)2-x(FedCoeMnf)y as the composition of nitrogen storage nanocomposite, combined with a composite preparation solution of step-by-step high-temperature smelting and ball milling nanoification, the existing solid hydrogen storage alloys have insufficient nitrogen storage capacity and wide powder particle size distribution under normal temperature conditions, and efficient automatic grading and rapid hydrogen absorption effect are achieved.
Patent Information
- Application Number
- CN202411609040.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing solid hydrogen storage alloys have insufficient hydrogen storage capacity under normal temperature conditions and have a wide distribution of powder particle size during production, which leads to difficulty in automatic grading and increases manual operation strength.
Tix(LaaCebMgc)2-x(FedCoeMnf)y is used as the composition of hydrogen storage nanocomposite material, and nanocomposite materials with high hydrogen storage capacity and automatic grading capabilities are prepared through a composite preparation scheme of step-by-step high-temperature smelting and ball milling nanoification.
It achieves a first-time hydrogen absorption capacity of more than 2.0 wt.% at room temperature, reduces the demand for manual grading, and improves production efficiency and material activation performance.
Smart Images

Figure CN119568990A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage, and in particular to a hydrogen storage nanocomposite material and powder preparation equipment and a preparation method. Background Art
[0002] As an energy source, hydrogen has the advantages of high calorific value, wide sources, clean and zero carbon. However, due to the disadvantages of low volume density and easy leakage of gaseous hydrogen, the large-scale storage and application of hydrogen energy are limited. In recent years, solid-state hydrogen storage technology based on reversible hydrogen absorption and desorption chemical reactions has become a research and development hotspot in the field of hydrogen energy applications due to its high volume density, safety and efficiency, and high purity of hydrogen release.
[0003] Commonly used solid hydrogen storage alloys include rare earth alloys, titanium alloys and magnesium alloys. Rare earth alloys are represented by LaNi5, with a saturated hydrogen absorption capacity of about 1.4wt.%, and have good activation performance, impurity resistance and suitable room temperature hydrogen absorption and desorption pressure; titanium alloys are represented by TiFe and TiMn2 alloys, with a saturated hydrogen absorption capacity of about 1.8wt.%, but they have the disadvantages of high activation pressure and weak impurity resistance respectively; magnesium-based hydrogen storage materials are represented by pure magnesium and Mg2Ni, with hydrogen storage capacities of 7.6wt.% and 4.3wt.%, respectively, but they have the disadvantages of high hydrogen absorption and desorption temperature (~300℃) and low hydrogen desorption pressure. In summary, there is currently a lack of solid hydrogen storage alloy materials that can be used at room temperature and have both high capacity and easy activation performance at normal pressure. Moreover, the production process of solid hydrogen storage alloy materials usually involves alloy powder making operations, and existing powder preparation methods include mechanical crushing and gas atomization. Gas atomization uses high-pressure gas (such as air, nitrogen or argon) to atomize molten metal. The characteristics of gas atomization are fast cooling speed, fine powder grains, high yield and low cost. However, the powder particle size distribution produced by gas atomization is usually wide, and the alloy powder cannot be automatically classified when discharged. Subsequent particle size classification requires manual work, which makes the work intensity of the staff greater and the operation is more troublesome. Summary of the invention
[0004] The purpose of the present invention is to provide a hydrogen storage nanocomposite material and a powder preparation device and a preparation method to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A hydrogen storage nanocomposite material, the composition of the hydrogen storage nanocomposite material is Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f )y , where the range of x is 1≤x≤1.5, the range of y is 1≤y≤1.5, the range of the sum of a+b+c is 1≤a+b+c≤1.2, and c≥0.5, the range of the sum of d+e+f is 1≤d+e+f≤1.05, and f≥0.5.
[0007] Preferably, the hydrogen storage nanocomposite material is composed of:
[0008] The composition of the hydrogen storage nanocomposite material is: Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 ; or Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 ;
[0009] Or Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 The hydrogen storage nanocomposite material can be activated to absorb hydrogen after being evacuated to a vacuum level below 0.5 Pa at room temperature and filled with 3 MPa of hydrogen pressure, and the initial hydrogen absorption amount is greater than or equal to 2.0 wt.%.
[0010] A powder preparation device for hydrogen storage nanocomposite materials, comprising a device body, support carriers symmetrically fixedly arranged on both sides of the device body, a support bottom ring fixedly arranged on the lower end of the support carrier, a feed pipe fixedly arranged on the upper end of the device body, and a discharge bottom opening is provided on the lower side of one end of the device body, a fixed receiving plate is fixedly arranged inside the device body corresponding to the discharge bottom opening, and a plurality of upper discharge openings are provided on the device body above the discharge bottom opening, and a partition carrier is fixedly arranged inside the device body corresponding to the upper discharge opening, grading holes are provided on the partition carrier, a connecting plate sleeve is fixedly arranged on the upper side of the discharge bottom opening and the upper discharge opening, a bearing matching plate is fixedly arranged on the connecting plate sleeve, and the bearing matching plate A supporting guide hole is provided on the top, and a plug-in movable hole is provided on the other end of the equipment body opposite to the bottom discharge port and the upper discharge port, a hydraulic rod is fixedly installed on the equipment body at the lower side of the plug-in movable hole, a load-bearing guide rod is fixedly arranged on the equipment body at the lower side of the hydraulic rod, a connecting carrier is fixedly arranged on the load-bearing guide rod, a stabilizing connecting plate is fixedly arranged on the upper end of the connecting carrier, and supporting matching plates are symmetrically fixedly arranged on both sides of the connecting carrier, a stabilizing socket is provided on the support matching plate, and a matching socket is provided at the bottom of the hole of the stabilizing socket, supporting strips are symmetrically fixedly arranged on both sides of the equipment body, a limiting guide rod is fixedly arranged on the support strip, and an automatic grading discharge mechanism is arranged on the equipment body.
[0011] Preferably, the automatic grading discharging mechanism includes a driving connecting plate frame, a bearing plate frame, a movable bearing plate and an installation bearing rod, and a lower end of the driving connecting plate frame is fixedly provided with a downward connecting plate, and the downward connecting plate is fixedly connected to the hydraulic rod, and a guide support hole is opened on the downward connecting plate, and a bearing guide rod is inserted into the guide support hole.
[0012] Preferably, protruding bearing plates are symmetrically fixed at both ends of the driving connecting plate frame, a connecting matching column is fixedly provided on one side of the protruding bearing plate, and a supporting bearing rod is fixedly provided on the other side of the protruding bearing plate, a matching rack is fixedly provided on the supporting bearing rod, and the connecting matching column is connected to the bearing plate frame.
[0013] Preferably, a plurality of supporting discs are fixedly provided on the supporting plate frame, a receiving box body is inserted into the supporting disc body, and a connecting plate is fixedly provided on the supporting disc body, a driving connecting rod is hinged on the connecting plate, a sealing supporting plate is hinged on the upper end of the driving connecting rod, a sealing plug-in plate is fixedly provided on the sealing supporting plate, the sealing plug-in plate is respectively inserted into the bottom outlet and the upper outlet when sealing the bottom outlet and the upper outlet, a guide supporting rod is also fixedly provided on the sealing supporting plate, the guide supporting rod is inserted into the supporting guide hole, and a connecting supporting block is fixedly provided on the guide supporting rod, and the connecting supporting block is hinged to the driving connecting rod.
[0014] Preferably, matching bearing plates are symmetrically fixed on both sides of the bearing plate frame, the matching bearing plates are provided with guide through holes, limiting guide rods are inserted in the guide through holes, and an L-shaped support plate is fixedly provided on the lower end of the matching bearing plate, a protruding support plate is fixedly provided on the L-shaped support plate, an upper top column is fixedly provided on the protruding support plate, a matching channel is also provided on the matching bearing plate, and an upward swing plate is fixedly provided on the end of the matching bearing plate away from the equipment body, a connecting channel is provided on the upward swing plate, and a connecting matching column is inserted in the connecting channel.
[0015] Preferably, a movable carrier plate is installed on the device body, a supporting connecting rod is fixedly provided on the movable carrier plate, the supporting connecting rod is inserted in the movable plug-in hole, and a pushing plate is fixedly provided on the supporting connecting rod, and the pushing plate is located inside the device body.
[0016] Preferably, mounting plates are symmetrically fixed on both sides of the movable carrier plate, mounting through holes are opened on the mounting plates, mounting rods are inserted in the mounting through holes, limiting blocks are fixedly provided at the lower ends of the mounting rods, the limiting blocks are inserted in the stabilizing holes, and a half gear is fixedly provided at the upper ends of the mounting rods.
[0017] A method for preparing a hydrogen storage nanocomposite material comprises the following steps:
[0018] Step 1: Smelting Ti, Fe, Co, Mn and La, Ce, Mg in a stoichiometric ratio into Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy respectively in an induction melting furnace, and preparing alloy powders with a particle size of less than 50 μm respectively;
[0019] Step 2: The Ti-Fe-Co-Mn alloy powder and the La-Ce-Mg alloy powder prepared in step 1 are mixed in a stoichiometric ratio and subjected to ball milling and mechanical alloying to obtain Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y A hydrogen storage nanocomposite material, wherein the value range of x is 1≤x≤1.5, the value range of y is 1≤y≤1.5, the range of the sum of a+b+c is 1≤a+b+c≤1.2, and c≥0.5, the range of the sum of d+e+f is 1≤d+e+f≤1.05, and f≥0.5.
[0020] Preferably, in step 2, the Ti-Fe-Co-Mn alloy powder and the La-Ce-Mg alloy powder are loaded into a planetary ball mill, the ball-to-material ratio during the ball milling process is 5:1-20:1, and the ball mill jar is evacuated to 1×10 -2 Pa, fill with 0.05-0.1MPa high-purity argon gas for ball milling, the ball milling speed is 500-1000 rpm, the ball milling time is 2-5 hours, and the Ti prepared in step 2 is x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y The hydrogen storage nanocomposite material is heat treated in a vacuum or inert gas atmosphere, and the heat treatment method is: Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y The hydrogen storage nanocomposite material was placed in a vacuum furnace and evacuated to a pressure of ≤1×10 -2 Pa, then introduce argon and control the gas pressure at 30-100 kPa, raise the temperature to 500-800 ° C, keep warm for 1-2 hours, and cool down along with the furnace.
[0021] Compared with the prior art, the invention has the following advantages:
[0022] 1. The alloy composition of the nanocomposite hydrogen storage material prepared by the present invention is precisely controllable and has a high hydrogen storage capacity. The ball milling process obtains a nanocrystalline structure alloy, which has a fast hydrogen atom diffusion rate and a high hydrogen absorption and desorption rate. Moreover, the ball milling process introduces more grain defects, resulting in a higher catalytic active surface. Furthermore, the hydrogen storage alloy produced by the present invention can be activated by hydrogen filling at room temperature after being evacuated by a mechanical pump, and quickly reaches an initial hydrogen absorption capacity of more than 2.0wt.%, thereby having a high hydrogen absorption mass ratio. In addition, the hydrogen absorption and desorption platform of the alloy is adjusted by adjusting the ratio of Fe and Mn elements, and a series of alloys whose hydrogen desorption platforms can be matched with chemical energy storage, fuel cells, etc. are prepared, which can achieve the adjustment of the hydrogen absorption and desorption platform, and the nanocomposite material has high activity and self-catalytic surface properties with excellent activation performance. The alloy can be contacted with hydrogen to achieve one-time activation after being evacuated to 0.1Pa.
[0023] 2. A plurality of partition plates are arranged inside the equipment body, and grading holes are opened on the partition plates. The size of the grading holes on the upper partition plate is larger than that on the lower partition plate. In this way, the powder can be automatically graded in the process of falling down after powder forming, without the need for manual grading operation at a later stage, which is very convenient.
[0024] 3. When discharging, start the hydraulic rod, and the connecting plate frame is driven to move under the action of the hydraulic rod. As the connecting plate frame moves, the carrying plate frame can be driven to move upward, and then the receiving box body is driven to move up to the bottom discharge port and the upper discharge port respectively to facilitate the receiving of the powder. Under the action of the carrying plate frame, the sealing carrier plate will be driven to move so that the bottom discharge port and the upper discharge port are in an open state to facilitate discharging. At this time, the connecting plate sleeve, the receiving box body and the sealing carrier plate form a closed space to ensure that the powder is stably collected in the receiving box body.
[0025] 4. In addition, when the receiving box reaches the working point, as the driving connecting plate frame continues to move, it will unlock the movable carrier plate. At the same time, with the cooperation of the rack and the half gear, it will drive the movable carrier plate to move, and then drive the pushing plate to move, so that the powder can be pushed into the receiving box body for graded collection. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 Schematic diagram of room temperature activation hydrogen absorption curve of hydrogen storage nanocomposites.
[0027] Figure 2 Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 Schematic diagram of the isothermal hydrogen absorption and desorption curves of hydrogen storage nanocomposites at 25°C.
[0028] Figure 3 Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn0.5 ) 1.2 Schematic diagram of hydrogen absorption curve of hydrogen storage nanocomposites activated at room temperature.
[0029] Figure 4 Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 Schematic diagram of the isothermal hydrogen absorption and desorption curves of hydrogen storage nanocomposites at 25°C.
[0030] Figure 5 Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Schematic diagram of room temperature activation hydrogen absorption curve of hydrogen storage nanocomposites.
[0031] Figure 6 Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Schematic diagram of the isothermal hydrogen absorption and desorption curves of hydrogen storage nanocomposites at 25°C.
[0032] Figure 7 This is a schematic diagram of the room temperature activated hydrogen absorption curve of the hydrogen storage nanocomposite material provided in Comparative Example 1.
[0033] Figure 8 This is a first-person perspective diagram of the device assembly.
[0034] Fig. 9 A second perspective diagram of the device assembly.
[0035] Fig.10 for Fig. 9 A magnified schematic diagram of center A.
[0036] Fig.11 This is a schematic diagram of the structure of the device from the first perspective.
[0037] Fig.12 for Fig.11 A magnified schematic diagram of point B in the middle.
[0038] Fig.13 It is a schematic diagram of the second perspective structure of the device body.
[0039] Fig.14 for Fig.13 Enlarged schematic diagram of point C in the middle.
[0040] Fig.15 It is a schematic diagram of the assembly of the driving connecting plate frame, the bearing plate frame 4, the movable carrier plate 5 and the mounting carrier rod 6.
[0041] Fig.16 for Fig.15 Enlarged schematic diagram of point D in the middle.
[0042] In the figure: 1. Equipment body; 10. Support carrier plate; 101. Support bottom ring; 11. Feed pipe; 12. Discharge bottom port; 121. Fixed material receiving plate; 13. Upper discharge port; 14. Separation carrier plate; 15. Grading hole; 16. Connecting plate sleeve; 161. Bearing matching plate; 162. Support guide hole; 17. Plug-in movable hole; 18. Hydraulic rod; 19. Bearing guide rod; 191. Connecting carrier; 192. Stable connecting plate; 193. Support matching plate; 194. Stable plug hole; 195. Matching plug hole; 2. Support strip; 21. Limiting guide rod; 3. Drive connecting plate frame; 31. Lower extension connecting plate; 32. Guide support hole; 33. Protruding bearing plate; 34 , connecting and matching column; 35, supporting load rod; 36, matching rack; 4, load-bearing plate frame; 41, supporting disc body; 42, receiving box body; 43, connecting connecting plate; 44, driving connecting rod; 45, sealing load plate; 46, sealing plug-in plate; 47, guiding load rod; 48, connecting load block; 49, matching load plate; 491, guiding through hole; 492, L-shaped support plate; 493, protruding support plate; 494, upper column; 495, matching channel; 496, upward plate; 497, connecting channel; 5, movable load plate; 51, supporting connecting rod; 52, pushing material plate; 53, installing load plate; 54, installing through hole; 6, installing load rod; 61, limiting plug block; 62, half gear. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] See also Figures 1 to 16 , the present invention provides a technical solution:
[0045] A hydrogen storage nanocomposite material, the composition of the hydrogen storage nanocomposite material is Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y , where the range of x is 1≤x≤1.5, the range of y is 1≤y≤1.5, the range of the sum of a+b+c is 1≤a+b+c≤1.2, and c≥0.5, the range of the sum of d+e+f is 1≤d+e+f≤1.05, and f≥0.5.
[0046] The Ti element is the main hydrogen absorbing component, and the preferred value range of x is 1-1.5. By adding La, a lanthanum-rich micro-region with rapid hydrogen absorption capability can be formed on the surface of the material, thereby improving the initial activation performance and subsequent kinetic performance of the alloy.
[0047] Adding Ce can reduce the oxygen impurity content in the alloy smelting process and adjust the alloy's resistance to impurity poisoning.
[0048] Adding an appropriate amount of Mg element can improve the overall hydrogen absorption capacity ratio of the alloy. The sum of the La, Ce, and Mg addition ratios a+b+c is controlled in the range of 1-1.2, and the Mg content that has a capacity-enhancing effect must exceed 0.5.
[0049] The ratio of Fe and Mn elements can adjust the hydrogen absorption and desorption platform pressure. The increase of Mn element content reduces the hydrogen absorption and desorption platform, while Co element can reduce the slope of the alloy hydrogen absorption and desorption platform, making the pressure of hydrogen absorption and desorption process more stable. The value range of the sum of Fe, Co and Mn content in d+e+f is 1-1.05, and f≥0.5.
[0050] Preferred alloys include: Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 ;Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 ; or Ti 1.4 (La 0.4 Ce0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 .
[0051] The preparation method of the above alloy specifically comprises the following steps:
[0052] Step 1: Calculate the amount of each alloy element according to the selected alloy composition, and weigh the corresponding metal raw materials for batching.
[0053] Step 2: Smelt Ti, Fe, Co, Mn and La, Ce, Mg into Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy respectively, and make metal powder with a particle size less than 50 μm. The specific preparation method can adopt the following mechanical powder making scheme or gas atomization powder making scheme:
[0054] Mechanical milling solution
[0055] The alloy is melted by vacuum induction and mechanically crushed. The alloy is stacked in a melting crucible according to the principle of high melting point elements at the bottom and low melting point and volatile elements at the top. The system is evacuated to a pressure of ≤1×10 -2 Pa and continue to evacuate for more than 30 minutes. At the same time, the alloy is heated to about 500°C at low power to fully desorb the impurity gases on the alloy surface; then high-purity argon is introduced, the pressure is controlled at 20-40kPa, and the smelting power supply is adjusted to full power for heating to fully melt the alloy.
[0056] The Ti-Fe-Co-Mn smelting temperature is controlled at 1650±10°C. After complete melting, the input power of the induction power supply is reduced. After refining at 1550°C±10°C for 10 minutes, it is cast into a water-cooled mold. After cooling, a block alloy with a length of about 10 cm and a width and thickness of about 5 cm is obtained.
[0057] The smelting temperature of the La-Ce-Mg alloy is controlled at 870±10°C. After the raw materials are completely melted, the power is reduced to control the temperature at 780±10°C for refining for 10 minutes, and then cast into a water-cooled mold. After cooling, a block alloy with a length of about 10 cm and a width and thickness of about 5 cm is obtained.
[0058] The above block alloy is crushed by jaw crusher and ball mill equipment protected by argon atmosphere and sieved into alloy powder with a particle size less than 50 μm for standby use.
[0059] Gas atomization powder making solution
[0060] The method adopts a vacuum inert gas atomization system to melt, refine and degas the alloy in a vacuum induction melting furnace, and places the molten alloy into a gas atomization nozzle system through a tundish, and atomizes the alloy using an inert gas. The specific implementation plan is as follows: the alloy is stacked in a melting crucible according to the principle of high melting point elements at the bottom and low melting point and volatile elements at the top, and the system is evacuated to a pressure of ≤1×10 -2 Pa and continue to evacuate for more than 30 minutes. At the same time, the alloy is heated to about 500°C at low power to fully desorb the impurity gases on the alloy surface; then high-purity argon is introduced, the pressure is controlled at 20-40kPa, and the smelting power supply is adjusted to full power for heating to fully melt the alloy.
[0061] The Ti-Fe-Co-Mn smelting temperature is controlled at 1650±10℃. After complete melting, the input power of the induction power supply is reduced and the alloy is refined at 1550℃±10℃ for 10 minutes. The cyclone collection system of the gas atomization system is turned on, and the alloy steel liquid is injected into the preheated tundish. At the same time, the tundish atomization nozzle is opened, and the alloy liquid in the tundish is sprayed out of the nozzle through the argon gas flow to form droplets. The droplets are cooled and collected in the cyclone collector, and finally an alloy powder with a particle size of less than 50μm is obtained.
[0062] The smelting temperature of La-Ce-Mg alloy is controlled at 870±10℃. After the raw materials are completely melted, the power is reduced to control the temperature at 820±10℃ for refining for 10 minutes. The cyclone collection system of the gas atomization system is turned on, and the alloy steel liquid is injected into the preheated tundish. At the same time, the tundish atomization nozzle is opened, and the alloy liquid in the tundish is sprayed out of the nozzle through the argon gas flow to form droplets. The droplets are cooled and collected in the cyclone collector, and finally an alloy powder with a particle size of less than 50μm is obtained.
[0063] The particle size screening equipment in the above two powder making schemes are all existing. In order to facilitate the screening of alloy powder after being crushed by jaw crusher and ball mill in the above mechanical powder making, or to facilitate the screening of metal powder alloy collected by cyclone collector in aerosol powder making, a new improved powder making equipment is proposed. The powder alloy particle size screening equipment can be used for further accurate classification and screening of alloy powder screened by the above two schemes. Its specific structure is as follows:
[0064] A powder preparation device for hydrogen storage nanocomposite materials comprises a device body 1, support carriers 10 are symmetrically fixedly arranged on both sides of the device body 1, a support bottom ring 101 is fixedly arranged on the lower end of the support carrier 10, a feed pipe 11 is fixedly arranged on the upper end of the device body 1, and a discharge bottom opening 12 is provided on the lower side of one end of the device body 1, a fixed material receiving plate 121 is fixedly arranged inside the device body 1 corresponding to the discharge bottom opening 12, and a plurality of upper discharge openings 13 are provided on the device body 1 above the discharge bottom opening 12, and a partition carrier 14 is fixedly arranged inside the device body 1 corresponding to the upper discharge opening 13, a grading hole 15 is provided on the partition carrier 14, and the size of the grading hole 15 on the upper partition carrier 14 is larger than the size of the grading hole 15 on the lower partition carrier 14, a connecting plate sleeve 16 is fixedly arranged on the upper side of the discharge bottom opening 12 and the upper discharge opening 13, and a fixed connecting plate sleeve 16 is fixedly arranged on the connecting plate sleeve 16 A load-bearing matching plate 161 is provided, and a supporting guide hole 162 is provided on the load-bearing matching plate 161. A plug-in movable hole 17 is provided on the other end of the equipment body 1 opposite to the discharge bottom port 12 and the upper discharge port 13. A hydraulic rod 18 is fixedly installed on the equipment body 1 at the lower side of the plug-in movable hole 17, and a load-bearing guide rod 19 is fixedly provided on the equipment body 1 at the lower side of the hydraulic rod 18. A connecting carrier 191 is fixedly provided on the load-bearing guide rod 19, and a stabilizing connecting plate 192 is fixedly provided on the upper end of the connecting carrier 191, and support matching plates 193 are symmetrically fixedly provided on both sides of the connecting carrier 191, a stabilizing plug hole 194 is provided on the support matching plate 193, and a matching plug hole 195 is provided at the bottom of the stabilizing plug hole 194, and support strips 2 are symmetrically fixedly provided on both sides of the equipment body 1, and a limiting guide rod 21 is fixedly provided on the support strips 2, and an automatic grading discharge mechanism is provided on the equipment body 1.
[0065] The automatic grading discharging mechanism includes a driving connecting plate frame 3, a bearing plate frame 4, a movable bearing plate 5 and an installed bearing rod 6. A lower end of the driving connecting plate frame 3 is fixedly provided with a lower connecting plate 31, which is fixedly connected to the hydraulic rod 18, and a guide support hole 32 is opened on the lower connecting plate 31, and a bearing guide rod 19 is inserted into the guide support hole 32.
[0066] The two ends of the driving connecting plate frame 3 are symmetrically fixed with protruding bearing plates 33, one side of the protruding bearing plate 33 is fixed with a connecting matching column 34, and the other side of the protruding bearing plate 33 is fixed with a supporting bearing rod 35, the supporting bearing rod 35 is fixed with a matching rack 36, and the connecting matching column 34 is connected to the bearing plate frame 4.
[0067] A plurality of support plates 41 are fixedly arranged on the carrier plate frame 4, a receiving box body 42 is plugged into the support plate body 41, and a connecting plate 43 is fixedly arranged on the support plate body 41, a driving connecting rod 44 is hinged on the connecting plate 43, a sealing carrier plate 45 is hinged on the upper end of the driving connecting rod 44, and a sealing plug-in plate 46 is fixedly arranged on the sealing carrier plate 45, and the sealing plug-in plate 46 is respectively plugged into the bottom outlet 12 and the upper outlet 13 when sealing the bottom outlet 12 and the upper outlet 13. In the discharge bottom opening 12 and the upper discharge opening 13, a guide bearing rod 47 is fixedly provided on the sealing carrier plate 45, and the guide bearing rod 47 is inserted in the support guide hole 162, and a connecting carrier block 48 is fixedly provided on the guide bearing rod 47, and the connecting carrier block 48 is hinged to the driving connecting rod 44. In addition, when the sealing plug-in plate 46 seals the discharge bottom opening 12 and the upper discharge opening 13, the sealing carrier plate 45 contacts the outer end surface of the equipment body 1.
[0068] The two sides of the supporting plate frame 4 are symmetrically fixed with matching supporting plates 49, and the matching supporting plates 49 are provided with guide through holes 491, in which the limiting guide rods 21 are inserted, and an L-shaped supporting plate 492 is fixedly provided at the lower end of the matching supporting plate 49, and a protruding supporting plate 493 is fixedly provided on the L-shaped supporting plate 492, and an upper top column 494 is fixedly provided on the protruding supporting plate 493, and a matching channel 495 is also provided on the matching supporting plate 49, and an upward-swinging plate 496 is fixedly provided on the end of the matching supporting plate 49 away from the equipment body 1, and a connecting channel 497 is provided on the upward-swinging plate 496, and a connecting matching column 34 is inserted in the connecting channel 497, and the inner wall of the connecting channel 497 is in contact with the connecting matching column 34, and the width of the connecting channel 497 is equal to the height of the matching channel 495.
[0069] A movable carrier plate 5 is installed on the equipment body 1, and a supporting connecting rod 51 is fixedly provided on the movable carrier plate 5. The supporting connecting rod 51 is inserted into the movable plug-in hole 17, and a pushing plate 52 is fixedly provided on the supporting connecting rod 51. The pushing plate 52 is located inside the equipment body 1. The surface of the pushing plate 52 is smooth and free of burrs, and can push the powder on the partition carrier 14 and the fixed receiving plate 121.
[0070] The movable carrier plate 5 is symmetrically fixed with mounting plates 53 on both sides, and the mounting plates 53 are provided with mounting through holes 54, in which mounting carrier rods 6 are inserted, and the lower end of the mounting carrier rod 6 is fixedly provided with a limiting plug block 61, which is inserted into the stabilizing socket 194, and the upper end of the mounting carrier rod 6 is fixedly provided with a half gear 62, and the size of the limiting plug block 61 is equal to the storage of the stabilizing socket 194, and is larger than the size of the matching socket 195.
[0071] During the forming process, the powder falls onto the partition carrier 14. The powder with a size larger than the size of the grading hole 15 stays on the partition carrier 14, and the powder with a size smaller than the size of the grading hole 15 passes through the grading hole 15 and falls to the next partition carrier 14. The smallest powder falls onto the fixed receiving plate 121, thereby realizing automatic grading without manual grading, which is very convenient. When discharging, the hydraulic rod 18 is started to drive the connecting plate frame 3 to move toward the direction of the equipment body 1, so that the connecting matching column 34 and the connecting The channel 497 cooperates with the support plate frame 4 to move upward, thereby driving the receiving box body 42 to move upward and plug it into the connecting plate sleeve 16. As the support plate frame 4 moves upward, the sealing carrier plate 45 will be driven to move under the action of the connecting plate 43, so that the sealing plug-in plate 46 is no longer plugged into the discharge bottom opening 12 and the upper discharge opening 13, thereby making the discharge bottom opening 12 and the upper discharge opening 13 in an open state, and as the receiving box body 42 moves upward, it will contact the corresponding sealing plug-in plate 46, so that The connecting plate sleeve 16, the sealing carrier plate 45 and the receiving box body 42 form a relatively closed space, which is convenient for the powder to fall into the receiving box body 42. When the connecting matching column 34 is inserted into the matching channel 495, the carrier plate frame 4 will no longer move upward. During the upward movement of the carrier plate frame 4, the upper push column 494 will be inserted into the matching socket 195 and contact the limit plug 61, thereby pushing the half gear 62 to move upward. In this way, when the connecting matching column 34 is inserted into the matching channel 495, the half gear 62 is just in contact with the matching rack 3. 6 is meshed, and at this time the limit plug 61 just exits the stabilizing socket 194 and contacts the upper end surface of the supporting matching plate 193, the movable carrier plate 5 is in an unlocked state, and under the cooperation of the half gear 62 and the matching rack 36, the movable carrier plate 5 and the driving connecting plate frame 3 are in a fixed connection state, so that under the action of the driving connecting plate frame 3, the movable carrier plate 5 can be driven to move, and then the pushing plate 52 can be driven to move, and the alloy powder can be pushed into the receiving box body 42, so that the graded collection is very convenient.
[0072] When setting up the above-mentioned screening and preparation equipment, it is sufficient to ensure that the aperture of the grading hole 15 is 50um. At this time, when the alloy powder with a particle size less than 50um roughly selected by the two traditional methods is discharged once through the above-mentioned equipment, the metal powder with a particle size less than 50um can be more accurately screened out from the above-mentioned roughly selected powder; and then used for the preparation of nano-composite materials in the following steps.
[0073] Step 3: The Ti-Fe-Co-Mn alloy powder prepared above is mixed with the La-Ce-Mg alloy powder according to the stoichiometric ratio and ball milled to achieve mechanical alloying, and finally a Ti alloy with the designed composition is prepared. x (La a Ce b Mg c ) 2-x (Fed Co e Mn f ) y Hydrogen storage nanocomposite materials, the specific ball milling process is:
[0074] (1) According to Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y Weigh alloy powders in the required ratio of Ti-Fe-Co-Mn alloy to La-Ce-Mg alloy;
[0075] (2) Loading the two alloy powder raw materials into a planetary ball mill, loading stainless steel grinding balls of appropriate quality according to the ball-to-material ratio, the ball-to-material ratio range is 5:1-20:1, sealing the ball mill jar and placing it in the ball mill station and locking it;
[0076] (3) Evacuate the ball mill to 1×10 -2 After the argon is filled with 0.05-0.1MPa high purity argon, the ball milling speed is 500-1000 rpm, and the ball milling time is 2-5 hours. x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y Nanocomposites for hydrogen storage.
[0077] Step 4: Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y The specific operation process of heat treatment of hydrogen storage nanocomposites is as follows:
[0078] (1) Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) yThe hydrogen storage nanocomposite material was placed in a vacuum heat-treated quartz tube and evacuated to a pressure of ≤1×10 -2 Pa, then argon is introduced and the pressure is controlled at 30-100 kPa;
[0079] (2) Turn on the heating power of the heat treatment furnace, set the heat treatment temperature and heat it. The heat treatment temperature is 500-800°C, keep it warm for 1-2 hours, and then cool it down with the furnace;
[0080] (3) The cooled Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y The hydrogen storage nanocomposite material is taken out and sealed and stored under the protection of inert gas.
[0081] The main hydrogenating elements of the alloy are light elements such as Ti and Mg, and the alloy has a relatively high hydrogen storage capacity of 1.85wt.%.
[0082] The heat treatment atmosphere is vacuum or inert gas, and the heat treatment method is:
[0083] Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y The hydrogen storage nanocomposite material was placed in a vacuum furnace and evacuated to a pressure of ≤1×10 -2 Pa, then introduce argon and control the gas pressure at 30-100 kPa, raise the temperature to 500-800 ° C, keep warm for 1-2 hours, and cool down along with the furnace.
[0084] Example 1
[0085] Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 Preparation of nanocomposites.
[0086] Preparation of alloy raw materials:
[0087]
[0088] Taking the preparation of 100kg alloy as an example, weigh the metal raw materials according to the data in the above table.
[0089] Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy smelting:
[0090] A 100kg-class vacuum induction melting furnace with a rated power of 200kW is used to smelt Ti-Fe-Co-Mn alloy:
[0091] a. Charging the furnace: Load the weighed Ti, Fe, Co and Mn into the crucible of the induction melting furnace in sequence, keeping Ti and Fe at the bottom of the furnace, Co in the middle and Mn at the top of the crucible. After loading, close the furnace cover;
[0092] b. Vacuuming: Turn on the vacuum system and evacuate the furnace to a vacuum of 1×10 -2 Pa, and maintain for 30 minutes;
[0093] c. Drying: Turn on the heating system, adjust the heating power to 60-100kW, heat the metal raw materials and continue to vacuum for about 30 minutes;
[0094] d. Filling with argon: Open the argon filling valve and fill the furnace with argon until the pressure reaches about 30kPa;
[0095] e. Melting: Adjust the heating power to about 180kW, and continue to heat the metal raw materials until the alloy is completely melted. At this time, the infrared temperature is about 1650±10℃;
[0096] f. Refining: Reduce the heating power to about 100kW, keep the alloy steel liquid in the range of 1550±10℃, and refine for 10min;
[0097] g. Casting: adjust the heating power to below 40kW, tilt the crucible, and allow the alloy steel liquid to be uniformly poured into the water-cooled mold through the pouring channel. As the amount of molten steel decreases, gradually adjust the heating power to 0 to complete the casting process.
[0098] h. Cooling and collecting materials: Turn off the heating power, keep the water cooling system on, cool the furnace body and the alloy in the water-cooled mold to room temperature, and open the furnace to collect materials.
[0099] A 50kg-class vacuum induction melting furnace with a rated power of 100kW is used for La-Ce-Mg alloy smelting:
[0100] a. Loading the furnace: Load the weighed La, Ce and Mg into the crucible of the induction melting furnace in sequence, keeping La at the bottom of the furnace, Ce in the middle and Mg at the top of the crucible. After loading, close the furnace cover;
[0101] b. Vacuuming: Turn on the vacuum system and evacuate the furnace to a vacuum of 1×10 -2Pa, and maintain for 30 minutes;
[0102] c. Drying: Turn on the heating system, adjust the heating power to 40-50kW, heat the metal raw materials and continue to vacuum for about 30 minutes;
[0103] d. Filling with argon: Open the argon filling valve and fill the furnace with argon until the pressure is about 40kPa;
[0104] e. Melting: Adjust the heating power to about 90kW, and continue to heat the metal raw materials until the alloy is completely melted. At this time, the infrared temperature is about 870±10℃;
[0105] f. Refining: Reduce the heating power to about 50kW, keep the alloy steel liquid at 820±10℃, and refine for 10min;
[0106] g. Casting: adjust the heating power to below 30kW, tilt the crucible, and allow the alloy steel liquid to be uniformly poured into the water-cooled mold through the pouring channel. As the amount of molten steel decreases, gradually adjust the heating power to 0 to complete the casting process.
[0107] h. Cooling and collecting materials: Turn off the heating power, keep the water cooling system on, cool the furnace body and the alloy in the water-cooled mold to room temperature, and open the furnace to collect materials.
[0108] Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy powder making:
[0109] The Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy are pulverized by jaw crusher-ball mill combined pulverizing equipment:
[0110] a. Loading: Load the alloy blocks into the silo on the upper part of the jaw crusher;
[0111] b. Gas replacement: purge the entire equipment with argon gas until the oxygen content in the system drops below 5000ppm;
[0112] c. Start crushing: Turn on the jaw crusher-ball mill power system. The material blocks in the silo enter the jaw crusher section through the vibrating feeder and are crushed into particles with a particle size less than 0.2mm. They are then transported to the ball mill equipment and crushed into fine powder below 50 microns, which are then sieved and collected into the material barrel.
[0113] Preparation of Ti by Mixed Ball Milling of Ti-Fe-Co-Mn Alloy and La-Ce-Mg Alloy 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 )1.15 Nanocomposites for hydrogen storage:
[0114] a. Mixing: weigh Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy powders in proportion and mix them evenly using a mixer. In this embodiment, the mass ratio of the two alloys is 2.202:1;
[0115] b. Loading: Weigh the mixed powder and grinding balls according to the capacity of the ball mill, load them into the ball mill jar and seal them. In this embodiment, the ratio of grinding balls to materials is 8:1. Load the ball mill jar into the ball mill and lock it;
[0116] c. Vacuuming and gas protection: Vacuum the ball mill to 1×10 -2 Pa, then filled with argon protective gas, the argon pressure is 0.1MPa;
[0117] d. Ball milling: Turn on the ball mill, set the speed to 900 rpm, and ball mill for 2 h to achieve mechanical alloying of the mixed powder under the action of ball milling;
[0118] e. Cooling and material collection: The ball mill will heat up during operation. After the ball mill is finished, you need to wait until the ball mill cools down to room temperature, open the ball mill, and collect the materials into sealed bags under the protection of inert gas.
[0119] Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 Thermal treatment of hydrogen storage nanocomposites:
[0120] a. Loading the furnace:
[0121] Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 The hydrogen storage nanocomposite material was placed in a vacuum heat-treated quartz tube and evacuated to a pressure of ≤1×10 -2 Pa, followed by argon
[0122] Gas and control the gas pressure to 60kPa;
[0123] b. Turn on the heating power of the heat treatment furnace, set the heat treatment temperature and heat it. The heat treatment temperature is 800℃, keep it warm for 1h, and then cool it down with the furnace;
[0124] c. Cool the Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 The hydrogen storage nanocomposite material is taken out and sealed and stored under the protection of inert gas.
[0125] Ti 1.25 (La 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 Hydrogen storage nanocomposite material hydrogen absorption and desorption performance test:
[0126] Weigh 1g of hydrogen storage material and put it into the sample chamber of the hydrogen absorption and desorption test device. Turn on the vacuum pump to evacuate the sample to less than 0.5Pa and keep it for 1h. Then, fill the sample with 3MPa high-purity hydrogen (purity 99.995% hydrogen) at room temperature (25℃). The room temperature hydrogen absorption activation curve of the material is as follows: Figure 1 As shown, the material begins to absorb hydrogen rapidly after a short incubation period, and the initial amount of hydrogen absorbed is about 2.0 wt.%.
[0127] After the material was repeatedly vacuumed and hydrogen was absorbed three times, its isothermal hydrogen absorption and desorption curve (PCT curve) was tested at 25°C. Figure 2 As shown in the figure, it can be seen that the material can begin to absorb a large amount of hydrogen at a hydrogen pressure of 1MPa, and the hydrogen absorption amount at a hydrogen pressure of 2MPa is higher than 1.80w%, and the saturated hydrogen storage capacity is higher than 1.9wt.%.
[0128] Example 2
[0129] Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 Preparation of nanocomposites.
[0130] In this embodiment, the aerosolization scheme is used.
[0131] Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 )0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 Preparation of nanocomposites.
[0132] Preparation of alloy raw materials
[0133]
[0134] Taking the preparation of 50kg of nanocomposite materials as an example, the metal raw materials are weighed according to the data in the above table.
[0135] Preparation of Ti-Fe-Co-Mn and La-Ce-Mg alloy powders:
[0136] Ti-Fe-Co-Mn alloy powder was prepared using a 50kg-class vacuum inert gas atomization furnace with a rated power of 100kW:
[0137] a. Charging the furnace: Load the weighed Ti, Fe, Co and Mn into the crucible of the induction melting furnace in sequence. After charging, the order of the raw materials in the crucible from bottom to top is Ti, Fe, Co and Mn. After the charging is completed, close the furnace cover;
[0138] b. Vacuuming: Turn on the vacuum system and evacuate the furnace to a vacuum of 1.0×10 -2 Pa, and maintain for 30 minutes;
[0139] c. Drying: Turn on the heating system, adjust the heating power to 30-40kW, heat the metal raw materials and continue to vacuum for about 30 minutes;
[0140] d. Filling with argon: Open the argon filling valve and fill the furnace with argon until the pressure reaches about 30kPa;
[0141] e. Melting: Adjust the heating power to about 90kW, and continue to heat the metal raw materials until the alloy is completely melted. At this time, the infrared temperature is about 1650±10℃;
[0142] f. Refining: Reduce the heating power to about 70kW, keep the alloy steel liquid in the range of 1550±10℃, and refine for 10min;
[0143] g. Gas atomization powder making: Turn on the cyclone collection system of the gas atomization system, adjust the heating power to less than 30 kW, tilt the crucible to inject the alloy steel liquid into the preheated tundish, and at the same time open the tundish atomization nozzle, adjust the argon gas input pressure to 120 kPa, and spray the alloy liquid in the tundish from the nozzle through the argon gas flow to form droplets, which are cooled and collected in the cyclone collector, that is, when discharging, the powder falls on the partition plate 14 inside the equipment body 1, and grading holes are opened on the partition plate 14. The size of the grading holes 15 on the upper partition plate 14 is larger than the size of the grading holes 15 on the lower partition plate 14, so that the automatic grading of the powder can be achieved in the process of the powder forming and falling, without the need for manual grading operation in the later stage, and finally a Ti-Fe-Co-Mn alloy powder with a particle size of less than 50 microns is obtained.
[0144] h. Cooling and collecting materials: Turn off the heating power, keep the water cooling system open, cool the alloy powder in the furnace body and cyclone collection system to room temperature, and open the furnace to collect materials.
[0145] The La-Ce-Mg alloy powder was prepared using a 50kg-class vacuum inert gas atomization furnace with a rated power of 100kW:
[0146] a. Furnace loading: Load the weighed La, Ce and Mg into the crucible of the induction melting furnace in sequence. After loading, the order of the raw materials in the crucible is La, Ce and Mg from bottom to top. After loading, close the furnace cover;
[0147] b. Vacuuming: Turn on the vacuum system and evacuate the furnace to a vacuum of 1×10 -2 Pa, and maintain for 30 minutes;
[0148] c. Drying: Turn on the heating system, adjust the heating power to 30-40kW, heat the metal raw materials and continue to vacuum for about 30 minutes;
[0149] d. Filling with argon: Open the argon filling valve and fill the furnace with argon until the pressure is about 40kPa;
[0150] e. Melting: Adjust the heating power to about 90kW, and continue to heat the metal raw materials until the alloy is completely melted. At this time, the infrared temperature is about 870±10℃;
[0151] f. Refining: Reduce the heating power to about 50kW, keep the alloy steel liquid at 820±10℃, and refine for 10min;
[0152] g. Gas atomization powder making: Turn on the cyclone collection system of the gas atomization system, adjust the heating power to less than 30 kW, tilt the crucible to inject the alloy steel liquid into the preheated tundish, and at the same time open the tundish atomization nozzle, adjust the argon gas input pressure to 120 kPa, and spray the alloy liquid in the tundish from the nozzle through the argon gas flow to form droplets, which are cooled and collected in the cyclone collector, that is, when discharging, the powder falls on the partition plate 14 inside the equipment body 1, and grading holes are opened on the partition plate 14. The size of the grading holes 15 on the upper partition plate 14 is larger than the size of the grading holes 15 on the lower partition plate 14, so that the automatic grading of the powder can be achieved in the process of the powder forming and falling, without the need for manual grading operation in the later stage, and finally the La-Ce-Mg alloy powder with a particle size of less than 50 microns is obtained.
[0153] h. Cooling and collecting materials: Turn off the heating power, keep the water cooling system open, cool the alloy powder in the furnace body and cyclone collection system to room temperature, and open the furnace to collect materials.
[0154] Preparation of Ti by ball milling of Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy powder 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 Nanocomposites:
[0155] a. Mixing: weigh Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy powders in proportion and mix them evenly using a mixer. In this embodiment, the mass ratio of the two alloys is 1.622:1;
[0156] b. Loading: weigh the mixed powder and grinding balls according to the capacity of the ball mill, load them into the ball mill jar and seal them. In this embodiment, the ratio of grinding balls to materials is 10:1. Load the ball mill jar into the ball mill and lock it;
[0157] c. Vacuuming and gas protection: Vacuum the ball mill to 1.0×10 -2 Pa, then filled with argon protective gas, the argon pressure is 0.1MPa;
[0158] d. Ball milling: Turn on the ball mill, set the speed to 800 rpm, and ball mill for 4 hours to achieve mechanical alloying of the mixed powder under the action of ball milling;
[0159] e. Cooling and material collection: The ball mill will heat up during operation. After the ball mill is finished, you need to wait until the ball mill cools down to room temperature, open the ball mill, and collect the materials into sealed bags under the protection of inert gas.
[0160] Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 Thermal treatment of hydrogen storage nanocomposites:
[0161] a. Loading: Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 The hydrogen storage nanocomposite material was placed in a vacuum heat-treated quartz tube and evacuated to a pressure of ≤1×10 -2 Pa, then argon was introduced and the pressure was controlled at 80 kPa;
[0162] b. Turn on the heating power of the heat treatment furnace, set the heat treatment temperature and heat it. The heat treatment temperature is 700℃, keep it warm for 2h, and then cool it down with the furnace;
[0163] c. Cool the Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 The hydrogen storage nanocomposite material is taken out and sealed and stored under the protection of inert gas.
[0164] Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 Hydrogen storage nanocomposite material hydrogen absorption and desorption performance test:
[0165] Weigh 1g of hydrogen storage material and put it into the sample chamber of the hydrogen absorption and desorption test device. Turn on the vacuum pump to evacuate the sample to below 0.5Pa and keep it for 1 hour. Then, fill the sample with 3MPa high-purity hydrogen (purity 99.995% hydrogen) at room temperature. The room temperature hydrogen absorption activation curve of the material is as follows: Figure 3 As shown, the material begins to absorb hydrogen rapidly after a short incubation period, and the initial amount of hydrogen absorbed is about 2.0 wt.%.
[0166] After the material was repeatedly vacuumed and hydrogen was absorbed three times, its isothermal hydrogen absorption and desorption curve (PCT curve) was tested at 25°C. Figure 4 As shown, the hydrogen absorption platform of the material is about 2MPa, the hydrogen absorption within 3MPa is higher than 1.60w%, and the saturated hydrogen storage is higher than 1.75wt.%.
[0167] Example 3
[0168] Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Preparation of nanocomposites.
[0169] In this embodiment, the aerosolization scheme is used.
[0170] Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Preparation of nanocomposites.
[0171] Preparation of alloy raw materials
[0172]
[0173] Taking the preparation of 50kg of nanocomposite materials as an example, the metal raw materials are weighed according to the data in the above table.
[0174] Preparation of Ti-Fe-Co-Mn and La-Ce-Mg alloy powders:
[0175] Ti-Fe-Co-Mn alloy powder was prepared using a 50kg-class vacuum inert gas atomization furnace with a rated power of 100kW:
[0176] a. Charging the furnace: Load the weighed Ti, Fe, Co and Mn into the crucible of the induction melting furnace in sequence. After charging, the order of the raw materials in the crucible from bottom to top is Ti, Fe, Co and Mn. After the charging is completed, close the furnace cover;
[0177] b. Vacuuming: Turn on the vacuum system and evacuate the furnace to a vacuum of 1.0×10 -2 Pa, and maintain for 30 minutes;
[0178] c. Drying: Turn on the heating system, adjust the heating power to 30-40kW, heat the metal raw materials and continue to vacuum for about 30 minutes;
[0179] d. Filling with argon: Open the argon filling valve and fill the furnace with argon until the pressure reaches about 30kPa;
[0180] e. Melting: Adjust the heating power to about 90kW, and continue to heat the metal raw materials until the alloy is completely melted. At this time, the infrared temperature is about 1650±10℃;
[0181] f. Refining: Reduce the heating power to about 70kW, keep the alloy steel liquid in the range of 1550±10℃, and refine for 10min;
[0182] g. Gas atomization powder making: Turn on the cyclone collection system of the gas atomization system, adjust the heating power to less than 30 kW, tilt the crucible to inject the alloy steel liquid into the preheated tundish, and at the same time open the tundish atomization nozzle, adjust the argon gas input pressure to 120 kPa, and spray the alloy liquid in the tundish from the nozzle through the argon gas flow to form droplets, which are cooled and collected in the cyclone collector, that is, when discharging, the powder falls on the partition plate 14 inside the equipment body 1, and grading holes are opened on the partition plate 14. The size of the grading holes 15 on the upper partition plate 14 is larger than the size of the grading holes 15 on the lower partition plate 14, so that the automatic grading of the powder can be achieved in the process of the powder forming and falling, without the need for manual grading operation in the later stage, and finally a Ti-Fe-Co-Mn alloy powder with a size less than 50 microns is obtained.
[0183] h. Cooling and collecting materials: Turn off the heating power, keep the water cooling system open, cool the alloy powder in the furnace body and cyclone collection system to room temperature, and open the furnace to collect materials.
[0184] The La-Ce-Mg alloy powder was prepared using a 50kg-class vacuum inert gas atomization furnace with a rated power of 100kW:
[0185] a. Furnace loading: Load the weighed La, Ce and Mg into the crucible of the induction melting furnace in sequence. After loading, the order of the raw materials in the crucible is La, Ce and Mg from bottom to top. After loading, close the furnace cover;
[0186] b. Vacuuming: Turn on the vacuum system and evacuate the furnace to a vacuum of 1.0×10 -2 Pa, and maintain for 30 minutes;
[0187] c. Drying: Turn on the heating system, adjust the heating power to 30-40kW, heat the metal raw materials and continue to vacuum for about 30 minutes;
[0188] d. Filling with argon: Open the argon filling valve and fill the furnace with argon until the pressure is about 40kPa;
[0189] e. Melting: Adjust the heating power to about 90kW, and continue to heat the metal raw materials until the alloy is completely melted. At this time, the infrared temperature is about 870±10℃;
[0190] f. Refining: Reduce the heating power to about 50kW, keep the alloy steel liquid at 820±10℃, and refine for 10min;
[0191] g. Gas atomization powder making: Turn on the cyclone collection system of the gas atomization system, adjust the heating power to less than 30kW, tilt the crucible to inject the alloy steel liquid into the preheated tundish, and at the same time open the tundish atomization nozzle, adjust the argon gas input pressure to 120kPa, and spray the alloy liquid in the tundish from the nozzle through the argon gas flow to form droplets, which are cooled and collected in the cyclone collector, that is, when discharging, the powder falls on the partition plate 14 inside the equipment body 1, and grading holes are opened on the partition plate 14. The size of the grading holes 15 on the upper partition plate 14 is larger than the size of the grading holes 15 on the lower partition plate 14, so that the automatic grading of the powder can be achieved in the process of the powder forming and falling down, without the need for manual grading operation in the later stage, and finally a La-Ce-Mg alloy powder with a size less than 50 microns is obtained.
[0192] h. Cooling and collecting materials: Turn off the heating power, keep the water cooling system open, cool the alloy powder in the furnace body and cyclone collection system to room temperature, and open the furnace to collect materials.
[0193] Preparation of Ti by ball milling of Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy powder 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Nanocomposites:
[0194] a. Mixing: weigh Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy powders in proportion and mix them evenly using a mixer. In this embodiment, the mass ratio of the two alloys is 2.749:1;
[0195] b. Loading: Weigh the mixed powder and grinding balls according to the capacity of the ball mill, load them into the ball mill jar and seal them. In this embodiment, the ratio of grinding balls to materials is 15:1. Load the ball mill jar into the ball mill and lock it;
[0196] c. Vacuuming and gas protection: Vacuum the ball mill to 1.0×10-2 Pa, then filled with argon protective gas, the argon pressure is 0.06MPa;
[0197] d. Ball milling: Turn on the ball mill, set the speed to 500 rpm, and ball mill for 5 hours to achieve mechanical alloying of the mixed powder under the action of ball milling;
[0198] e. Cooling and material collection: The ball mill will heat up during operation. After the ball mill is finished, you need to wait until the ball mill cools down to room temperature, open the ball mill, and collect the materials into sealed bags under the protection of inert gas.
[0199] Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Thermal treatment of hydrogen storage nanocomposites:
[0200] a. Loading: Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 The hydrogen storage nanocomposite material was placed in a vacuum heat-treated quartz tube and evacuated to a pressure of ≤1×10 -2 Pa, then argon was introduced and the pressure was controlled at 50 kPa;
[0201] b. Turn on the heating power of the heat treatment furnace, set the heat treatment temperature and heat it. The heat treatment temperature is 500℃, keep it warm for 1.5h, and then cool it down with the furnace;
[0202] c. Cool the Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 The hydrogen storage nanocomposite material is taken out and sealed and stored under the protection of inert gas.
[0203] Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn0.7 ) 1.3 Hydrogen storage nanocomposite material hydrogen absorption and desorption performance test:
[0204] Weigh 1g of hydrogen storage material and put it into the sample chamber of the hydrogen absorption and desorption test device. Turn on the vacuum pump to evacuate the sample to below 0.5Pa and keep it for 1h. Then, fill the sample with 3MPa high-purity hydrogen (purity 99.995% hydrogen) at room temperature. The room temperature (25℃) hydrogen absorption activation curve of the material is as follows: Figure 5 As shown, the material begins to absorb hydrogen rapidly after a short incubation period, and the initial hydrogen absorption amount is about 2.06wt.%.
[0205] After the material was repeatedly vacuumed and hydrogen was absorbed three times, its isothermal hydrogen absorption and desorption curve (PCT curve) was tested at 25°C. Figure 6 As shown, the median value of the hydrogen absorption platform of the material is about 0.8MPa, the hydrogen absorption within 3MPa is higher than 1.80w%, and the saturated hydrogen storage is higher than 1.95wt.%.
[0206] Comparative Example 1
[0207] For the Ti described in Example 3 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Direct smelting preparation of hydrogen storage materials.
[0208] This comparative example is carried out using the conventional direct smelting scheme.
[0209] Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Preparation of hydrogen storage alloys. To verify the beneficial effects of the composite preparation scheme of step-by-step high-temperature smelting and ball-milling nano-processing of the present invention.
[0210] Preparation of alloy raw materials
[0211]
[0212]
[0213] Taking the direct smelting preparation of 50kg alloy as an example, weigh the metal raw materials according to the data in the above table.
[0214] Ti1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Direct smelting of alloys:
[0215] A 50kg vacuum induction melting furnace with a rated power of 100kW was used to melt Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 Direct smelting of alloys:
[0216] a. Charging the furnace: Load weighed Ti, Fe, Co, Mn, La, Ce, and Mg into the crucible of the induction melting furnace in sequence. After charging, the order of the raw materials in the crucible from bottom to top is Mg, Ce, La, Ti, Fe, Co, and Mn. After loading, close the furnace cover;
[0217] b. Vacuuming: Turn on the vacuum system and evacuate the furnace to a vacuum of 1.0×10 -2 Pa, and maintain for 30 minutes;
[0218] c. Drying: Turn on the heating system, adjust the heating power to 30-40kW, heat the metal raw materials and continue to vacuum for about 30 minutes;
[0219] d. Filling with argon: Open the argon filling valve and fill the furnace with argon until the pressure reaches about 30kPa;
[0220] e. Melting: Adjust the heating power to about 90kW, and continue to heat the metal raw materials until the alloy is completely melted. At this time, the infrared temperature is about 1450±10℃;
[0221] f. Refining: Reduce the heating power to about 70kW, keep the alloy steel liquid in the range of 1400±10℃, and refine for 10 minutes;
[0222] g. Casting: Cast the alloy material directly into a columnar mold to obtain alloy rods.
[0223] Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1Mn 0.7 ) 1.3 Hydrogen storage alloy hydrogen absorption and desorption performance test:
[0224] Weigh 1g of hydrogen storage material and put it into the sample chamber of the hydrogen absorption and desorption test device. Turn on the vacuum pump to evacuate the sample to below 0.5Pa and keep it for 1h. Then, fill the sample with 3MPa high-purity hydrogen (purity 99.995% hydrogen) at room temperature. The room temperature (25℃) hydrogen absorption activation curve of the material is as follows: Figure 7 As shown, the material has a long incubation period and a slow hydrogen absorption rate, with the initial hydrogen absorption amount being only 1.1 wt.%.
[0225] In this comparative example, the direct smelting method was used to prepare
[0226] Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 The composition of hydrogen storage alloys is severely segregated, which affects the hydrogen storage performance of the alloy.
[0227] Comparative Example 2
[0228] Ti element content is less than 1.0;
[0229] For example, Ti 0.8 (La 0.4 Ce 0.05 Mg 0.55 ) 1.2 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 The alloy was prepared in the same manner as in Example 1, and the hydrogen absorption capacity was only 0.95 wt %. The hydrogen absorption capacity of this material is low and it is not suitable for use as a high-capacity solid hydrogen storage material.
[0230] Ti element content is higher than 1.5;
[0231] For example, Ti 1.6 (La 0.4 Ce 0.05 Mg 0.55 ) 0.4 (Fe 0.40 Co 0.03 Mn 0.6 ) 1.15 The alloy was prepared in the same manner as in Example 1, and the hydrogen absorption capacity was only 0.82 wt %. The hydrogen absorption capacity of this material is low, and it is not suitable for use as a high-capacity solid hydrogen storage material.
[0232] In addition, the Fe-Co-Mn element ratio is kept unchanged, the overall Fe-Co-Mn content is reduced to less than 1.0, and the Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 0.9 The alloy was prepared in the same manner as in Example 2, and the hydrogen absorption capacity was only 1.05 wt %. The hydrogen absorption capacity of this material is low, and it is not suitable for use as a high-capacity solid hydrogen storage material.
[0233] Keep the Fe-Co-Mn element ratio unchanged and increase the overall Fe-Co-Mn content to above 1.5, such as Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.6 The alloy was prepared in the same manner as in Example 2, and the hydrogen absorption capacity was only 0.97 wt %. The hydrogen absorption capacity of this material is low, and it is not suitable for use as a high-capacity solid hydrogen storage material.
[0234] Hydrogen Storage Alloy A m B n The present invention is generally composed of a metal on the A side with high hydrogen binding ability and a metal on the B side with good hydrogen diffusion ability. The present invention proposes a nanocomposite hydrogen storage material with good activation performance and high hydrogen storage capacity by adjusting the composition of multiple elements on the A and B sides of the hydrogen storage alloy and optimizing the alloy preparation method. x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y Among the elements on the A side, Ti is the main element to improve the hydrogen capacity, La and Ce elements have the effect of adjusting the activation ability and improving the resistance to impurity poisoning, and the addition of a small amount of Mg can further improve the hydrogen storage mass ratio; among the elements on the B side, the adjustment of the hydrogen absorption and desorption platform pressure is achieved through the ratio of Fe and Mn elements, and Co element can reduce the slope of the alloy hydrogen absorption and desorption platform.
[0235] In alloy Ti x (La a Ce b Mgc ) 2-x (Fe d Co e Mn f ) y Among the constituent elements, the melting points of Ti, Fe, Co, and Mn are between 1660-1246°C, while the melting points of La, Ce, and Mg are between 921-649°C, and the melting point difference between the two groups of elements is as high as 1011°C. Due to the differences in the melting points and activities of the alloy elements, the low-melting-point elements La, Ce, and Mg are prone to oxidation, gasification, and reaction with the crucible at high temperatures during the traditional one-pot smelting process, resulting in burning, which affects the stability of the alloy composition. At the same time, serious segregation occurs during the solidification process, resulting in a decrease in the hydrogen absorption capacity of the material; in terms of hydrogen absorption activity, segregation oxidation on the alloy surface affects the initial hydrogen absorption activation performance, and the coarse grains formed by solidification also hinder the diffusion of hydrogen atoms, reducing the hydrogen absorption and desorption rate of the material. In view of the above problems, the present invention proposes a composite preparation scheme of step-by-step high-temperature smelting and ball milling nano-crystalization, that is, the materials are divided into two groups of alloys, Ti-Fe-Co-Mn and La-Ce-Mg, according to the melting point of the alloy elements, and different smelting processes are formulated for smelting and respectively made into coarse powders less than 50 μm; then the two groups of alloys are mechanically alloyed by ball milling, and Ti with a microscopic nano-grain structure is obtained by controlling the ball milling energy. x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y Nanocomposite materials.
[0236] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A hydrogen storage nanocomposite material, characterized in that: The composition of the hydrogen storage nanocomposite material is Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y , where the range of x is 1≤x≤1.5, the range of y is 1≤y≤1.5, the range of the sum of a+b+c is 1≤a+b+c≤1.2, and c≥0.5, the range of the sum of d+e+f is 1≤d+e+f≤1.05, and f≥0.
5.
2. The hydrogen storage nanocomposite material according to claim 1, characterized in that: The composition of the hydrogen storage nanocomposite material is: Tea 1.25 (Day 0.4 Ce 0.05 Mg 0.55 ) 0.75 (Fe 0.40 Co 0.03 Mr 0.6 ) 1.15 ; Or Ti 1.2 (La 0.5 Ce 0.1 Mg 0.5 ) 0.8 (Fe 0.45 Co 0.05 Mn 0.5 ) 1.2 ; Or Ti 1.4 (La 0.4 Ce 0.1 Mg 0.7 ) 0.6 (Fe 0.25 Co 0.1 Mn 0.7 ) 1.3 The hydrogen storage nanocomposite material can be activated to absorb hydrogen after being evacuated to a vacuum level below 0.5 Pa at room temperature and filled with 3 MPa of hydrogen pressure, and the initial hydrogen absorption amount is greater than or equal to 2.0 wt.%.
3. A powder preparation device for hydrogen storage nanocomposite material, characterized in that: The powder preparation device is used to produce the hydrogen storage nanocomposite material according to any one of claims 1 to 2, comprising a device body (1), support carriers (10) are symmetrically fixedly arranged on both sides of the device body (1), a support bottom ring (101) is fixedly arranged at the lower end of the support carrier (10), a feed pipe (11) is fixedly arranged at the upper end of the device body (1), and a discharge bottom opening (12) is opened at the lower side of one end of the device body (1), and the discharge bottom opening (12) corresponds to the internal fixed portion of the device body (1). A fixed material receiving plate (121) is provided, and a plurality of upper material discharge ports (13) are provided on the equipment body (1) above the material discharge bottom port (12), and a partition carrier plate (14) is fixedly provided inside the equipment body (1) corresponding to the upper material discharge ports (13), and the partition carrier plate (14) is provided with grading holes (15), and a connecting plate sleeve (16) is fixedly provided on the upper side of the material discharge bottom port (12) and the upper material discharge port (13), and a bearing matching plate (161) is fixedly provided on the connecting plate sleeve (16), and the bearing matching plate A support guide hole (162) is provided on the main body (161); a plug-in movable hole (17) is provided on the other end of the main body (1) opposite to the discharge bottom opening (12) and the upper discharge opening (13); a hydraulic rod (18) is fixedly installed on the main body (1) below the plug-in movable hole (17); a load-bearing guide rod (19) is fixedly provided on the main body (1) below the hydraulic rod (18); a connecting carrier (191) is fixedly provided on the load-bearing guide rod (19); and the connecting carrier (191) A stabilizing connecting plate (192) is fixedly arranged at the upper end, and supporting matching plates (193) are symmetrically fixedly arranged on both sides of the connecting carrier (191), a stabilizing plug hole (194) is provided on the supporting matching plate (193), and a matching plug hole (195) is provided at the bottom of the stabilizing plug hole (194), supporting strips (2) are symmetrically fixedly arranged on both sides of the equipment body (1), and a limiting guide rod (21) is fixedly arranged on the supporting strips (2), and an automatic grading discharging mechanism is arranged on the equipment body (1).
4. The powder preparation device for hydrogen storage nanocomposite material according to claim 3, characterized in that: The automatic grading discharging mechanism comprises a driving connecting plate frame (3), a bearing plate frame (4), a movable bearing plate (5) and a mounting bearing rod (6); a lower end of the driving connecting plate frame (3) is fixedly provided with a lower extending connecting plate (31); the lower extending connecting plate (31) is fixedly connected to a hydraulic rod (18); a guide support hole (32) is provided on the lower extending connecting plate (31); a bearing guide rod (19) is inserted into the guide support hole (32).
5. The powder preparation device for hydrogen storage nanocomposite material according to claim 4, characterized in that: The two ends of the driving connection plate frame (3) are symmetrically fixed with protruding bearing plates (33), one side of the protruding bearing plate (33) is fixed with a connecting matching column (34), and the other side of the protruding bearing plate (33) is fixed with a supporting bearing rod (35), a matching rack (36) is fixed on the supporting bearing rod (35), and the connecting matching column (34) is connected to the bearing plate frame (4).
6. The powder preparation device for hydrogen storage nanocomposite material according to claim 5, characterized in that: A plurality of support plates (41) are fixedly arranged on the carrier plate frame (4), a receiving box body (42) is plugged into the support plate body (41), and a connecting plate (43) is fixedly arranged on the support plate body (41), a driving connecting rod (44) is hingedly connected to the connecting plate (43), a sealing carrier plate (45) is hingedly connected to the upper end of the driving connecting rod (44), a sealing plug plate (46) is fixedly arranged on the sealing carrier plate (45), and the sealing plug plate (46) is fixedly arranged on the sealing carrier plate (45). The connecting plate (46) is respectively inserted into the bottom discharge opening (12) and the upper discharge opening (13) when sealing the bottom discharge opening (12) and the upper discharge opening (13). A guide bearing rod (47) is also fixedly provided on the sealing carrier plate (45). The guide bearing rod (47) is inserted into the supporting guide hole (162). A connecting bearing block (48) is fixedly provided on the guide bearing rod (47). The connecting bearing block (48) is hinged to the driving connecting rod (44).
7. The powder preparation device for hydrogen storage nanocomposite material according to claim 6, characterized in that: The two sides of the supporting plate frame (4) are symmetrically fixed with matching supporting plates (49), the matching supporting plates (49) are provided with guide through holes (491), and the limiting guide rods (21) are inserted in the guide through holes (491), and an L-shaped supporting plate (492) is fixedly provided at the lower end of the matching supporting plate (49), and a protruding supporting plate (493) is fixedly provided on the L-shaped supporting plate (492), and an upper top column (494) is fixedly provided on the protruding supporting plate (493), and a matching channel (495) is also provided on the matching supporting plate (49), and an upward-swinging plate (496) is fixedly provided at one end of the matching supporting plate (49) away from the equipment body (1), and a connecting channel (497) is provided on the upward-swinging plate (496), and a connecting matching column (34) is inserted in the connecting channel (497).
8. The powder preparation device for hydrogen storage nanocomposite material according to claim 7, characterized in that: A movable carrier plate (5) is mounted on the device body (1), a supporting connecting rod (51) is fixedly arranged on the movable carrier plate (5), the supporting connecting rod (51) is plugged into the plug-in movable hole (17), and a pushing material plate (52) is fixedly arranged on the supporting connecting rod (51), the pushing material plate (52) is located inside the device body (1), mounting carrier plates (53) are symmetrically fixedly arranged on both sides of the movable carrier plate (5), mounting through holes (54) are opened on the mounting carrier plates (53), mounting carrier rods (6) are plugged into the mounting through holes (54), a limiting plug block (61) is fixedly arranged at the lower end of the mounting carrier rod (6), the limiting plug block (61) is plugged into the stabilizing plug hole (194), and a half gear (62) is fixedly arranged at the upper end of the mounting carrier rod (6).
9. A method for preparing a hydrogen storage nanocomposite material, characterized in that: The preparation method is used to produce the hydrogen storage nanocomposite material according to any one of claims 1 to 2, comprising the following steps: Step 1: Smelting Ti, Fe, Co, Mn and La, Ce, Mg in a stoichiometric ratio into Ti-Fe-Co-Mn alloy and La-Ce-Mg alloy respectively in an induction melting furnace, and preparing alloy powders with a particle size of less than 50 μm respectively; Step 2: The Ti-Fe-Co-Mn alloy powder and the La-Ce-Mg alloy powder prepared in step 1 are mixed according to a stoichiometric ratio, and then subjected to ball milling and mechanical alloying to obtain Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y A hydrogen storage nanocomposite material, wherein the value range of x is 1≤x≤1.5, the value range of y is 1≤y≤1.5, the range of the sum of a+b+c is 1≤a+b+c≤1.2, and c≥0.5, the range of the sum of d+e+f is 1≤d+e+f≤1.05, and f≥0.
5.
10. The method for preparing a hydrogen storage nanocomposite material according to claim 9, characterized in that: In step 2, Ti-Fe-Co-Mn alloy powder and La-Ce-Mg alloy powder are loaded into a planetary ball mill. The ball-to-material ratio during the ball milling process is 5:1-20:
1. The ball mill is vacuumed to 1×10 -2 Pa, fill with 0.05-0.1MPa high-purity argon gas for ball milling, the ball milling speed is 500-1000 rpm, the ball milling time is 2-5 hours, and the Ti prepared in step 2 is x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y The hydrogen storage nanocomposite material is heat treated in a vacuum or inert gas atmosphere, and the heat treatment method is: Ti x (La a Ce b Mg c ) 2-x (Fe d Co e Mn f ) y The hydrogen storage nanocomposite material was placed in a vacuum furnace and evacuated to a pressure of ≤1×10 -2 Pa, then introduce argon and control the gas pressure at 30-100 kPa, raise the temperature to 500-800 ° C, keep warm for 1-2 hours, and cool down along with the furnace.
Citation Information
Patent Citations
Hydrogen absorbing and releasing alloy material and application thereof
CN101560625A
BCC type hydrogen storage alloy and preparation method and application thereof
CN118497580A
Hydrogen storage alloy / carbon nanometer tube composite hydrogen storage material
CN1259584A
Hydrogen storage alloy and its production
JP1997031575A
Cited By
Porous hydrogen storage material with hydrogen slow release function and hydrogen core preparation process thereof
CN120987258A
Method for controlling perfect sphericity degree of nano aluminum powder through plasma atomization
CN121755722A
A method for controlling perfect sphericity of nano-aluminum powder by plasma atomization
CN121755722B